Regulation and roles of Cdc7 kinase under replication stress - Yamada, Masayuki; Masai, Hisao; Bártek, Jiří (Cell Cycle, 2014)
Cdc7 (cell division cycle 7) kinase together with its activation subunit ASK (also known as Dbf4) play pivotal roles in DNA replication and contribute also to other aspects of DNA metabolism such as DNA repair and recombination. While the biological significance of Cdc7 is widely appreciated, the molecular mechanisms through which Cdc7 kinase regulates these various DNA transactions remain largely obscure, including the role of Cdc7-ASK/Dbf4 under replication stress, a condition associated with diverse (patho)physiological scenarios. In this review, we first highlight the recent findings on a novel pathway that regulates the stability of the human Cdc7-ASK/Dbf4 complex under replication stress, its interplay with ATR-Chk1 signaling, and significance in the RAD18-dependent DNA damage bypass pathway. We also consider Cdc7 function in a broader context, considering both physiological conditions and pathologies associated with enhanced replication stress, particularly oncogenic transformation and tumorigenesis. Furthermore, we integrate the emerging evidence and propose a concept of Cdc7-ASK/Dbf4 contributing to genome integrity maintenance, through interplay with RAD18 that can serve as a molecular switch to dictate DNA repair pathway choice. Finally, we discuss the possibility of targeting Cdc7, particularly in the context of the Cdc7/RAD18-dependent translesion synthesis, as a potential innovative strategy for treatment of cancer.
Keywords: DNA vazebné proteiny; oprava DNA; Animals; Stress, Physiological; DNA Damage; Chromatin; Neoplasms; nádory; lidé; replikace DNA; Protein Serine-Threonine Kinases; signální transdukce; DNA Repair; Signal Transduction; fyziologický stres; Cell Cycle Proteins; poškození DNA; Replication Origin; chromatin; DNA-Binding Proteins; replikační počátek; zvířata; DNA Replication; proteiny buněčného cyklu; protein-serin-threoninkinasy; Humans